She Said, He Said: Denise Scott Brown and Kenneth Frampton on Popular Taste - Deborah Fausch (Footprint, 2011)
During the post-war period, the nature of ‘the people’ and popular culture was a matter of intense interest to the disciplines of architecture and urban design. These issues stand behind a debate between Denise Scott Brown and Kenneth Frampton in the December 1971 issue of Casabella. The disagreement between Frampton and Scott Brown concerns three issues: the nature of ‘the people’, the character of popular culture, and the role of architects in relation to popular culture. Underlying this last issue is the question of popular taste: whether a debased devolution from that of the educated and cultured classes, or an embodiment of its own intrinsic principles.